MEASUREMENT OF HIGHER EDUCATION SERVIVE QUALITY USING HEDPERF AND HIEDQUAL IMPORTANCE PERFORMANCE ANALYSIS METHODS - Wati, Linda; Dharma, Surya; Jadmiko, Purbo; Sugiarti, Titin (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2024)
The image of a tertiary institution is indicated by the quality of service perceived by students because the quality of service can also reflect the academic and non-academic quality of a tertiary institution. There have been many studies focusing on measuring the quality of services in higher education (using the Serqual measurement), therefore, this study aims to measure quality services by combining other approaches, namely HEdPERF and HiEDQUAL. Bung Hatta University was used as the research object (n=370 students). The university was selected because it is a reputable private university which was founded under the name one of the nation's proclamator with significant influence. Based on the results of data analysis using the Importance Performance Analysis (IPA) technique, it can be concluded that aspects of academic facilities and support services are in the quadrant that exceeds student expectations. On the other hand, the campus infrastructure aspect should be the main priority that must receive immediate attention, followed by the reputation, academic and program aspects which are quadrant positions that must be maintained while the administrative service aspect is in low priority positionKeywords: Service Quality, Higher Education, IPA (Importance-Performance Analysis), HedPERF, HiEDQUAL